Forms of Citizens‘ Communication with the Public Administration Institutions - Stofkova, Jana; Gasova, Katarina (Communications - Scientific letters of the University of Zilina, 2017)
Globalisation and technological development have caused many changes that force both businesses and governments to react. The development of information and communication technologies has changed the way how people obtain information, communicate, work, buy goods and affect their everyday lives. The revolution of the Internet has opened new opportunities for all economic operators. This process can not be stopped. The government which wants to meet the citizens‘ changing demands and needs has to be flexible and adapt to this progress, which results in e-Government. The contribution focuses on the ways of communication between citizens and institutions of public administration and evaluates their satisfaction with provided e-Government services.